2021
DOI: 10.1002/jsfa.11343
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of biochar and biostimulants on nutrient and toxic element uptake by pepper in contaminated soils

Abstract: BACKGROUND Nowadays a significant amount of land contaminated with toxic elements is being used for agriculture, posing a serious risk of crop contamination and toxicity. Several methodologies are being used to remediate soil contamination, including the use of amendments such as biochar. This work evaluated the effects of biochar combined with different fertirrigations (water, a conventional fertilizer solution, or a fertilizer solution with a commercial biostimulant derived from leonardite) on the availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Biochar has the potential benefit of improving soil chemistry. 18 Biochar has a stable carbon structure and contains nutrients such as nitrogen, phosphorus and potassium, which indirectly increases soil nutrients. 25 Qi et al 27 found that biochar application effectively increased soil nitrogen, phosphorus, potassium and organic matter content, which increased with the amount of biochar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar has the potential benefit of improving soil chemistry. 18 Biochar has a stable carbon structure and contains nutrients such as nitrogen, phosphorus and potassium, which indirectly increases soil nutrients. 25 Qi et al 27 found that biochar application effectively increased soil nitrogen, phosphorus, potassium and organic matter content, which increased with the amount of biochar.…”
Section: Discussionmentioning
confidence: 99%
“…16 (2) It increases soil fertility and microorganism. Biochar contains a large amount of organic carbon, it can rapidly increase soil organic matter content and improve soil fertility, 17,18 and its strong adsorption capacity helps soil nutrient retention. 6,16 Moreover, biochar can stimulate microbial activity and diversity, promoting the healthy development of soil ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Es importante alimentar al girasol de acuerdo con sus necesidades, de modo que se pueda conseguir una alta calidad y rendimiento si se presta mucha atención a la cantidad y duración de las aplicaciones de fertilizantes minerales (Mahmood et al, 2022). Las cambiantes condiciones climáticas, combinadas con la contaminación, han provocado diversos estreses abióticos en los cultivos, incluido el girasol, que afectan a su calidad y rendimiento, la sinergia que producen los bioestimulantes favorecen la nutrición de los cultivos (Antón-Herrero et al, 2022). Entre los estreses abióticos, la salinidad ha afectado a la producción de girasol en varios países.…”
Section: Introductionunclassified
“…Biochar is a product of thermochemical transformation of plant (or animal) biomass, and its addition to soil can increase the content of carbon, nitrogen and phosphorus in soil, minimize the phytotoxic effects of contaminated soil, stimulate the soil microbial community, and improve growth and yield [8][9][10][11]. On a molecular level, biochar can be viewed as an engineered nanocomposite [12][13][14], which allows for direct comparison of effect of nanoparticles and biochar.…”
Section: Introductionmentioning
confidence: 99%